2012
DOI: 10.3856/vol40-issue4-fulltext-6
|View full text |Cite
|
Sign up to set email alerts
|

Organic matter characterization and decomposition dynamics in sub Antarctic streams impacted by invasive beavers

Abstract: ABSTRACT. Despite being a relatively remote and well conserved area, the sub-Antarctic ecoregion faces pressing global threats from climate change, the ozone hole and introduced species. Its freshwater ecosystems are one of the least studied components of this biome, but they are known to confront a host of invasive taxa including trout and beavers. We set out to understand the basic characterization and dynamics of organic matter processing and decomposition in sub-Antarctic streams under natural forest (NF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…By engineering new lentic habitats with greater retention than previous lotic zones, the overall BOM carbon budget in these benthic ecosystems increased by about 70% at the stream network scale. Previous research has shown that beaver‐induced increases in BOM affect stream food webs, enhancing secondary production of benthos by an order of magnitude (Anderson & Rosemond, ) and transitioning benthic production and BOM decomposition rates in sub‐Antarctic streams to values more similar to temperate zones (Anderson & Rosemond, ; Ulloa et al ., ). It should be noted, however, that the effects of beavers on other ecosystem functions need to be more fully explored, as our analyses have only focused on benthic ecosystems.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…By engineering new lentic habitats with greater retention than previous lotic zones, the overall BOM carbon budget in these benthic ecosystems increased by about 70% at the stream network scale. Previous research has shown that beaver‐induced increases in BOM affect stream food webs, enhancing secondary production of benthos by an order of magnitude (Anderson & Rosemond, ) and transitioning benthic production and BOM decomposition rates in sub‐Antarctic streams to values more similar to temperate zones (Anderson & Rosemond, ; Ulloa et al ., ). It should be noted, however, that the effects of beavers on other ecosystem functions need to be more fully explored, as our analyses have only focused on benthic ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, rather than concluding from these data that the invasive beaver is not harmful to TDF because it ‘merely’ engineers ponds whose benthic biodiversity is similar to natural lentic habitats, we can now more precisely determine the actual way it has transformed this landscape, which is via effects on ecosystem processes. Other studies have also shown that this invasive species not only changes standing crops, but increases decomposition rates of BOM (Ulloa et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beaver effects on benthic food webs are relevant at the landscape-scale in Tierra del Fuego's sub-Antarctic streams because, on average, they increased the retention of organic matter in watersheds by 72% (Anderson et al 2014), and they also increase the decomposition rate of N. pumilio leaves (Ulloa et al 2012). By integrating the present study's FA results to previous knowledge of sub-Antarctic limnology, we now can add several new insights and re-affirm other aspects of aquatic ecology in southern Patagonia.…”
Section: Discussionmentioning
confidence: 99%